Kdo me bo gledal? Socialna opora, zdravje in bolezen starejših ljudi - Pahor, Majda (Teorija in praksa, 2007)
Many studies around the world prove social support to be an important factor of illness prevention and health promotion. Most support in case of illness is provided by social networks, most commonly family. Friends, co-workers and neighbors are also important. Social support bears influence to physical, psychological and social dimensions of health, which gave rise to the interest to find out whether interventions can increase beneficial effects of social networks. The findings of these studies are not yet possible to be uniformly synthesized and generalized. Within the research project Social integration of the elderly in Slovenia, quantitative and qualitative data on social support of the elderly in case of illness for 2005 was gathered on a convenience sample. The data show the increase of the importance of family networks. Using qualitative methods, forms of help in case of illness related to the conceptualization of health were identified.
Keywords: socialna omrežja; družbena omrežja; starostniki; socialna opora; zdravje; bolezen; Slovenia; Slovenija; analiza omrežij